Repositioning the corporate criminal: comparing and contrasting corporate criminal liability in Canada and Finland - Anne Alvesalo-Kuusi; Steven Bittle; Liisa Lähteenmäki (United States, 2022)
Over the past two decades, a number of states in the Global North have introduced laws aimed at holding corporations criminally liable. While there is an important literature examining these legal regimes there is a paucity of comparative work interrogating the different political struggles and processes leading to corporate criminal liability (CCL) legislation. This paper addresses this lacuna by comparing and contrasting the development of CCL in Canada and Finland. By scrutinizing the law reform processes in each jurisdiction, the paper documents how CCL emerged under different conjunctures in each country, yet were shaped similarly by hegemonic beliefs in the non-criminal status of corporation, the importance of advancing private enterprise and established jurisprudence. Of particular note are the ways in which dominant notions of legal individualism and the universal legal subject constrained legislative efforts to hold corporations criminally to account therein preventing corporate misconduct from being processed as “real” crimes.